The impact of substituting water with eco enzyme in natural bar soap production - Ginting, Simparmin Br; Agustian, Muhammad Rizki; Darni, Yuli; Setiawan, Aris (Universitas Lambung Mangkurat, 2025)
The use of eco enzymes can enhance the quality of cleaning products, such as soap. These enzymes, including amylase, lipase, and protease, serve as catalysts and natural antibacterial agents, helping to break down carbohydrates, lipids, and proteins during the decomposition process. This study aims to evaluate the effect of adding eco enzymes on accelerating the saponification reaction and improving the quality of the produced bar soap. The method employed is the cold process, with variations of eco enzymes added at 0 g, 13 g, 26 g, and 39 g. All bar soap samples were analyzed according to the SNI 3532:2021 standard, and one sample that met this standard was selected for further enzymatic analysis. Of the five test parameters performed, soap products with the addition of 13 g, 26 g, and 39 g of eco enzymes complied with all SNI 3532:2021 standards. However, the soap with 0 g of eco enzymes did not meet one of the standards for total plate count microbe contamination, which produced a result of ≤ 4000 CFU/g. Additionally, lipase and protease enzymes were detected in the soap with the addition of 26 g of eco enzymes. The hardness levels of each soap variation were as follows: 1.3 N for 0 g, 1.7 N for 13 g, 2.03 N for 26 g, and 1.47 N for 39 g of eco enzymes.